Multiscale sterilizable 3D printed auricular templates to guide cartilaginous framework sizing and sculpture during autologous microtia reconstruction - Bushra Alhazmi, MBBS (JPRAS Open, 2021)
Summary: Microtia reconstruction using autologous costal cartilage can be one of the most challenging tasks in reconstructive surgery. An intraoperative guide using 2-dimentional drawing of the contralateral ear on an x-ray film remains the current standard of care. In this paper, we present the use of computer-aided design and desktop 3D printing to fabricate low cost, sterilizable auricular carving templates to serve as a peri-operative reference for microtia reconstruction. The design was made as a single component which incorporated the usual anatomic reference points of the ear based on Nagata technique as a Stereo-lithography file format (. STL) for 3D printing. The templates were created in sizes ranging from 55 mm to 70 mm with a 2 mm increment with an average production cost of 0.26 US dollars per material per template and about 4.5 US dollars for the whole set. Individual templates were then 3D-printed using a thermoplastic polyurethane (TPU 95A) semiflexible filament on a desktop fused deposition modeling, Ultimaker 2 + 3D printer. The produced template tolerated the sterilization process with no structural changes as compared to its pre-sterilization condition. In conclusion, we present cost-effective, sterilizable, multiscale auricular templates to guide the pre- and intra-operative carving of the cartilaginous framework during microtia reconstruction with more accuracy in a time efficient manner, thereby overcoming the drawbacks of using the traditional x-ray film. The templates are readily accessible and sharable for free through open-source software and can be directly 3D-printed using an affordable desktop 3D printer.